Characterization of a PA14 domain-containing galactofuranose-specific β-d-galactofuranosidase from Streptomyces sp. Issue 7 (3rd July 2017) - Matsunaga, Emiko; Higuchi, Yujiro; Mori, Kazuki; Yairo, Nao; Toyota, Saki; Oka, Takuji; Tashiro, Kosuke; Takegawa, Kaoru
Abstract: As a constituent of polysaccharides and glycoconjugates, β-d -galactofuranose (Gal f ) exists in several pathogenic microorganisms. Although we recently identified a β-d -galactofuranosidase (Gal f -ase) gene, ORF1110, in the Streptomyces strain JHA19, very little is known about the Gal f -ase gene. Here, we characterized a strain, named JHA26, in the culture supernatant of which exhibited Gal f -ase activity for 4-nitrophenyl β-d -galactofuranoside ( p NP-β-d -Gal f ) as a substrate. Draft genome sequencing of the JHA26 strain revealed a putative gene, termed ORF0643, that encodes Gal f -ase containing a PA14 domain, which is thought to function in substrate recognition. The recombinant protein expressed in Escherichia coli showed the Gal f -specific Gal f -ase activity and also released galactose residue of the polysaccharide galactomannan prepared from Aspergillus fumigatus, suggesting that this enzyme is an exo-type Gal f -ase. BLAST searches using the amino acid sequences of ORF0643 and ORF1110 Gal f -ases revealed two types of Gal f -ases in Actinobacteria, suggesting that Gal f -specific Gal f -ases may exhibit discrete substrate specificities. Abstract : : Gal f -specific Gal f -ases with discrete substrate recognition domains in Actinobacteria